Chiral analysis of α-diimine Ru(II) and Fe(II) complexes by capillary electrophoresis using sulfated cyclodextrins as stereoselectors - Sázelová, Petra; Koval, Dušan; Severa, Lukáš; Teplý, Filip; Kašička, Václav (Electrophoresis, 2017)
CE using randomly highly sulfated α-, β-, and γ-CDs (S-α-CD, S-β-CD, S-γ-CD), sulfobutylether-β-CD (SBE-β-CD), single isomer (6-O-sulfo) α-, β-, and γ-CDs, and their derivatives as stereoselectors was applied to chiral analysis of polypyridyl complexes of [Ru(bpy)3 ](2+) , [Ru(phen)3 ](2+) , and [Fe(phen)3 ](2+) (bpy = 2,2'-bipyridine; phen = 1,10 phenanthroline). The best separations of Δ- and Λ-enantiomers of the these complexes with high resolution (up to R1,2 = 7.0) and short analysis times (10-20 min) were achieved in the BGE composed of 22 mM NaOH/35 mM H3 PO4 , pH 2.4, containing 1.5-6.0 mM S-α-CD or S-β-CD, or SBE-β-CD as chiral selectors. The developed method was applied to the assessment of enantiomeric purity of several samples of [Ru(bpy)3 ](2+) catalyst. CE experiments were performed in a homemade analyzer equipped with bare or hydroxypropylcellulose-coated fused-silica capillaries (total/effective length 40/29 cm, id/od 50/375 μm) and an UV absorption detector operating at 206 nm. In addition to chiral analysis, apparent binding constants of the complexes of [Ru(bpy)3 ](2+) , [Ru(phen)3 ](2+) , and [Fe(phen)3 ](2+) enantiomers with five sulfated CDs (S-α-CD, S-β-CD, S-γ-CD, SBE-β-CD, and 16Me-8S-γ-CD) were determined from the dependence of their effective electrophoretic mobilities on the concentration of the CDs in the BGE by nonlinear regression analysis. Calculated apparent binding constants of these complexes were found to be in the (1.10-4.66) × 10(3) L/mol range. Moreover, it was shown that at selected concentrations of some S-CDs and suppressed or very low electroosmotic flow, the exceptional enantioseparations with infinite resolution could be achieved.
Keywords: stereoizomerie; Sulfates; pyridiny; cyklodextriny; sírany; Ruthenium; Stereoisomerism; železnaté sloučeniny; Ferrous Compounds; Electrophoresis, Capillary; Nonlinear Dynamics; Pyridines; nelineární dynamika; elektroforéza kapilární; ruthenium; Cyclodextrins